An exploratory study investigating the metabolic activity and local cytokine profile in patients with melanoma treated with pazopanib and paclitaxel. (19th September 2016) - Thurneysen, S.; Cheng, P.F.; Nagel, H.W.; Kunz, M.; Jaberg‐Bentele, N.; Nägeli, M.; Ziegler, M.; Guenova, E.; Goldinger, S.M.; Mangana, J.; Levesque, M.P.; Dummer, R.
Summary: Background: There is a medical need for new drugs in patients with BRAF wild‐type metastatic melanoma. Pazopanib is a multitarget tyrosine kinase inhibitor with antitumour and antiangiogenic activity. Objectives: The primary aim was to investigate the metabolic response to pazopanib monotherapy and pazopanib plus paclitaxel in patients with BRAF wild‐type melanoma. Secondary end points were the early cytokine and chemokine profiles and histological findings. Methods: Pazopanib (400 mg twice daily) was administered orally from days 1 to 10 and from days 14 to 70. An intravenous infusion with paclitaxel (150 mg m −2 body surface) was administered on days 14, 35 and 56. Metabolic response evaluation was performed before treatment, after treatment with pazopanib (day 10) and after treatment with pazopanib and paclitaxel (day 70). Skin biopsy of metastatic tissue for chemokine and cytokine expression analysis and histology and immunohistochemistry (CD68, CD163) evaluation, and blood samples were taken at the same time points. Results: Two patients failed screening and 17 were dosed. Of 67 adverse events, nine (13%) were grade 3 or 4. Five of 14 evaluable patients had a partial metabolic response at day 10 under pazopanib monotherapy. The response rate at day 70 under combined pazopanib–paclitaxel treatment was 0%. Immunohistochemistry revealed an increase of M2‐like macrophages in nonresponders compared with responders. We observed a significant upregulation of five cytokines (CXCL1, CXCL2, CXCL13, CCL22 and SPP1) in responding vs. nonresponding lesions. Overall, the median progression‐free survival was 70 days (range 5–331), which did not differ significantly between responders (148 days) and nonresponders (70 days, P = 0·17). Conclusions: In this patient population pazopanib efficacy was limited. Response is associated with low M2‐like macrophage density and increased expression of several chemokines. Abstract : What's already known about this topic? Increased expression of vascular endothelial growth factor (VEGF) and other tyrosine kinases leads to tumour promotion, associated with poor prognosis in patients with melanoma. Pazopanib is a multitarget tyrosine kinase inhibitor effective in several tumour types. Pazopanib is suggested to suppress VEGF effects and has shown some efficacy in melanoma. What does this study add? Pazopanib showed limited activity in patients with advanced melanoma. Responding tumours demonstrated high expression of several chemokines and cytokines. Resistant tumours showed high numbers of tumour‐associated M2‐like macrophages. What is the translational message? Systemic therapy with the multikinase inhibitor pazopanib results in profound alterations of the microenvironment in metastatic melanoma, including the cytokine–chemokine network. A primary effect is documented on tumour‐associated macrophages, which might protect the tumour cell population from pazopanib‐induced growth inhibition and cell death.